DINAMIKA PERADABAN DAN PEMIKIRAN ISLAM PADA MASA DINASTI UMAYYAH DAN ABBASIYAH : SUATU KAJIAN HISTORIS-FILOSOFIS - Nurjuman, Iman; Ulan Sri Anggraeni; Mochammad Irfan Fachrurozi; Ismi Hasyudi; Masripah; M. Tajudin Zuhri; Nenden Munawaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the dynamics of Islamic civilization and thought during the Umayyad and Abbasid dynasties through a historical-philosophical lens. The Umayyad Dynasty is noted for its political and administrative achievements that significantly expanded Islamic territories. In contrast, the Abbasid Dynasty is recognized as a hub of scientific, philosophical, and cultural development, ushering in the golden age of Islamic intellectualism. This research employs a qualitative method with a literature review approach, drawing upon academic sources published within the last five years. Findings reveal that both dynasties played crucial roles in establishing the foundation of a holistic Islamic civilization. The Umayyads emphasized political and military expansion, while the Abbasids significantly contributed to scientific and cultural advancements. The study concludes that the development of Islamic thought cannot be separated from the historical and political contexts of the time, and was further enriched by interactions with other civilizations such as the Greeks and Persians. These findings are expected to contribute to the development of contemporary Islamic civilization studies.